Konsep Wisata Mandiri sebagai Arahan Penyusunan Masterplan Desa Gunung Batu Kabupaten Banjar Kal-Sel - Ira Mentayani; Prima Widia Wastuty; Muhammad Ibnu Saud; Bani Noor Muchamad (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Gunung Batu Village is located in Connect Makmur District, Banjar Regency and requires direction and guidance in village development and development. This village needs guidelines and priority design plans to support the village self-reliance program. This priority design plan includes village infrastructure and roads in the three village hamlets that connect various social, cultural and economic activities. This village has various potentials, but this village does not yet have a development scheme, a thematic direction of growth, and indicators to increase this potential. Therefore, this community service program aims to contribute the idea of a master plan for Gunung Batu Village. Through this master plan, it is hoped that a comprehensive, integrated, and sustainable picture of village self-reliance plans and programs will be obtained with a common interest for the residents of Gunung Batu Village so that the community is able to manage village potential and village development programs independently. The results of this activity are in the form of a Gunung Batu Village master plan which has gone through an evaluation process and then handed over from the community service team of FT ULM to the Gunung Batu Village Head as a form of accountability for this activity.